The Problems Of Integrated Science Learning (Use Of Learning Media Reviewed From The Teacher Aspect) - Nora Alisa Pulungan; Dharma Gyta Sari Harahap; Kasmawati (CV. Inara, 2021)
The role of media in learning process is the one of indicator that influences student learning outcomes. In terms of developing instructional media, the role of educators is the most decisive thing that compiled media can convey the contents of learning material well to students. So, the educator skills in terms of the use of instructional media it’s very necessary, especially in science learning. The purpose of this study are (1) to analyze the problems felt by the teacher in the field of integrated science studies in the Utilization of Learning Media; (2) knowing the causes of the problems faced by the teacher in the use of media in the learning process and (3) to providing solutions for the existing problems to overcome the problems that faced by the teacher in the field of integrated science studies.Descriptive qualitative method is the method that used in this study with data collection techniques direct interviews with teachers in Junior High School Number 6 in Padangsidimpuan, and observation while the learning goes on. The results showed there some problems felt by teachers in the use of media in the learning process, that’s : (1) lack of motivation by school principal to teachers;(2) training on making learning media has never been followed by teachers; (3) not all of teachers have an awareness of the importance of learning media; (4) lack of time owned by teachers in terms of preparing the media that they will use; (5) lack of teacher knowledge in terms of developing existing learning media ;(6) teachers are less concerned with the use of media when teaching and learning process in the classroom and more of them only rely the text books in the learning process; and (7)Evaluation of teacher performance in the classroom is rarely done.